Period of time taken by Brachiaria humidicola (Rendle) Scheweick seed to complete germination - De Aquino Tomaz, Camila [UNESP]; Martins, Cibele Chalita [UNESP]; Da Silva, Givanildo Zildo [UNESP]; Vieira, Roberval Daiton [UNESP] (Universidade Estadual de Londrina, 2016)
The period of 21 days suggested by the Brazilian Rules for Seed Testing for the germination test of B. humidicola seeds seems too long for seed producing companies and laboratories since they depend on the results for decisions concerning the storage or the commercialization of the seed lots. So, the objective of this work was to evaluate the possibility of getting germination results of B. humidicola seeds in a shorter period. The procedures consisted in submitting the seeds to a dormancy breaking treatment and to alternating temperatures during the germination test. Seed samples of nineteen S1 and S2 seed lots were submitted to the following treatments: moistening the germination substratum with 1) deionized water (check treatment), 2) a KNO3 (0.2%) solution, and 3) scarifying the seeds with sulfuric acid for 10 minutes. The germination test was conducted under the conditions of 1) alternating temperatures of 20 and 35 °C and 2) alternating temperatures of 15 and 35 °C both with 8 hours of light. Normal seedlings were evaluated in daily countings. The results showed that the germination test of B. humidicola seeds may be carried out under alternating temperatures of 15 and 35 °C without breaking seed dormancy with a final evaluation of the germination 10 days after the sowing of the seeds.
Keywords: Dormancy; Forage grass; Pasture; Temperature